The role of life meaningfulness on the quarter-life crisis of university students in Indonesia's new capital - Habibie, Alfiesyahrianta; Sholichatun, Yulia; Tri Rahayu, Iin (Institut Agama Islam Negeri Langsa, 2023)
The policy of moving the national capital from Jakarta to East Kalimantan has caused pros and cons. The government is trying to equalize the economy. However, the younger generation, namely students, are still plagued by problems, namely quarter-life crisis, which has an impact on their mental health. This study examines the role of meaningfulness of life on the quarter-life crisis in students living in Indonesia's new capital city. This research design is a simple linear regression with purposive sampling to 511 students (n = 511) who study or come from East Kalimantan. Data was collected through Robbinson's Developmental Crisis Questionnaire (DCQ-12) Scale instrument and Stegger's Meaning in Life Questionnaire scale students. The results showed a significant effect of meaning in life on quarter-life crisis in college students. However, there are differences in the influence of its aspects, namely the presence of meaning and searching for meaning aspects of a quarter-life crisis. Therefore, individuals find significant value in undergoing a crisis to rise to become new individuals who are meaningful in life.